Mechanical behaviour of polymer derived ceramics – a review. (18th August 2021) - Sujith, Ravindran; Jothi, Sudagar; Zimmermann, Andre; Aldinger, Fritz; Kumar, Ravi
ABSTRACT: Since the last five decades, polymer-derived ceramics (PDCs) are in use and envisaged for a variety of applications. The transition of a precursor to an inorganic ceramic by pyrolysis and heat-treatment results in either amorphous or nanocrystalline composites with the evolution of phases strongly controlled by the processing conditions. Understanding the deformation behaviour under ambient conditions and at elevated temperatures is key to designing these materials for long-term use. However, quantitative reliable estimation of mechanical properties is quite challenging due to its unique structure which in turn is strongly governed by the precursor chemistry. The mechanical behaviour of PDCs in the form of fibres, bulk and foams are different and they are discussed separately. Both experimental and simulation-based studies are considered in this review. Recently, additive manufacturing processes have been used for the fabrication of PDCs, the mechanical properties of which are also included in this review.